Pengaruh Promosi Kesehatan Keluarga Terhadap Peran Keluarga Dalam Pengelolaan Anggota Keluarga Dengan Diabetes Mellitus Di Puskesmas Kebakkrmat I - Yeni Nur Rahmayanti (Universitas Duta Bangsa Surakarta, 2020)
There are 90% diabetes mellitus sufferers in the world. Diabetes mellitus (DM) is a degenerative disease that has increased every year in countries. Diabetes Mellitus if not handled properly will lead to complications. Cooperation between patients and families is expected to prevent chronic complications of DM, by providing information through health promotion. In this study using